Genetic modification of hearing in tubby mice: evidence for the existence of a major gene (moth1) which protects tubby mice from hearing loss - Ikeda, Akihiro (1999)
Quantitative trait locus (QTL) analysis of genetic crosses has proven to be a useful tool for identifying loci associated with specific phenotypes and for dissecting genetic components of complex traits. Inclusion of a mutation that interacts epistatically with QTLs in genetic crosses is a unique and potentially powerful method of revealing the function of novel genes and pathways. Although we know that a mutation within the novel tub gene leads to obesity and cochlear and retinal degeneration, the biological function of the gene and the mechanism by which it induces its phenotypes are not known. In the current study, a QTL analysis for auditory brainstem response (ABR) thresholds, which indicates hearing ability, was performed in tubby mice from F(2) intercrosses between C57BL/6J-tub/tub and AKR/J-+/+ F(1), hybrids (AKR intercross) and between C57BL/6J-tub/tub and CAST/Ei.B6-tub/tub F(1) hybrids (CAST intercross). A major QTL, designated as modifier of tubby hearing1 (moth1), was identified on chromosome 2 with a LOD score of 33.4 (P <; 10(−33)) in the AKR intercross (181 mice) and of 6.0 (P <; 10(−6)) in the CAST intercross (46 mice). This QTL is responsible for 57 and 43% of ABR threshold variance, respectively, in each strain combination. In addition, a C57BL/6J congenic line carrying a 129/Ola segment encompassing the described QTL region when made homozygous for tubby also exhibits normal hearing ability. We hypothesize that C57BL/6J carries a recessive mutation of the moth1 gene which interacts with the tub mutation to cause hearing loss in tub/tub mice. A moth1 allele from either AKR/J, CAST/Ei or 129/Ola is sufficient to protect C57BL/6J-tub/tub mice from hearing loss.